Quantifying added drag in swimming with parachutes: implications for resisted swimming training - Coloretti, V.; Fantozzi, S.; Gatta, G.; Bonifazi, M.; Zamparo, P.; Cortesi, M. (The Journal of Strength and Conditioning Research, 2025)
Swimming parachutes are often used during training as resistive equipment, but their added load and the hydrodynamic effects of the swimmer in front have yet to be investigated. This study explores the drag coefficient (k) of 4 commercial parachutes with different sizes under 3 conditions: (a) when towed without a swimmer in front (kpara), (b) pulled by a passive (streamlined) swimmer (kPpara), and (c) pulled by an actively propelling swimmer (kApara). An electromechanical device was used to assess kpara and kPpara as the ratio between towing force and the square of towing velocity during 5 trials at different velocities while kApara was measured based on full-tethered and semi-tethered forces using the residual thrust methods. The values of kpara were as follows: 15.4 ± 0.1, 19.7 ± 0.1, 37.2 ± 0.1, and 73.9 ± 2.8 N·s2·m-2 for parachutes with surfaces of 400, 529, 900, and 1,600 cm2, respectively. Parachute resistance decreased by approximately 21% when pulled by a passive swimmer, whereas it increased by about 15% when pulled by a propelling swimmer. Possible explanations for these differences include drafting and added mass effects. Data reported in this study can assist coaches in quantifying the added load of swimming parachutes during training, by knowing only the parachute size and the swimming velocity.